2002
DOI: 10.1016/s0045-6535(02)00240-0
|View full text |Cite
|
Sign up to set email alerts
|

Combustion sources of particles: 2. Emission factors and measurement methods

Abstract: Emissions from the combustion of biomass and fossil fuels are a significant source of particulate matter (PM) in ambient outdoor and/or indoor air. It is important to quantify PM emissions from combustion sources for regulatory and control purposes in relation to air quality. In this paper, we review emission factors for several types of important combustion sources: road transport, industrial facilities, small household combustion devices, environmental tobacco smoke, and vegetation burning. We also review cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(27 citation statements)
references
References 54 publications
1
26
0
Order By: Relevance
“…Biomass smoke contains a wide spectrum of potentially health damaging pollutants that include coarse, fine, and ultrafine particles, carbon monoxide (CO), oxide of nitrogen and sulfur, transition metals, polycyclic aromatic hydrocarbons, volatile organic compounds and bio-aerosols http://dx.doi.org/10.1016/j.ijsbe.2014.11.002 2212-6090/Ó 2014 The Gulf Organisation for Research and Development. Production and hosting by Elsevier B.V. Morawska, 2002;Smith et al, 2000). Recent studies (Mondal et al, 2013;Dasgupta et al, 2006) in rural households had shown that indoor air pollution is due to combustion of biomass fuels.…”
Section: Introductionmentioning
confidence: 99%
“…Biomass smoke contains a wide spectrum of potentially health damaging pollutants that include coarse, fine, and ultrafine particles, carbon monoxide (CO), oxide of nitrogen and sulfur, transition metals, polycyclic aromatic hydrocarbons, volatile organic compounds and bio-aerosols http://dx.doi.org/10.1016/j.ijsbe.2014.11.002 2212-6090/Ó 2014 The Gulf Organisation for Research and Development. Production and hosting by Elsevier B.V. Morawska, 2002;Smith et al, 2000). Recent studies (Mondal et al, 2013;Dasgupta et al, 2006) in rural households had shown that indoor air pollution is due to combustion of biomass fuels.…”
Section: Introductionmentioning
confidence: 99%
“…The quantification of particulate emissions from combustion sources is important for multiple reasons including generation of emission inventories for the development of air management and control strategies, examination of specific sources on compliance with standards, and assessment of personal and environmental exposures (Zhang and Morawska, 2002). Because many of the health and climate effects associated with atmospheric particles are influenced by size, particle emission factors should also be size resolved.…”
Section: Introductionmentioning
confidence: 99%
“…The main sources contributing to outdoor air pollution are combustion sources, including vehicle emissions, industrial combustion, biomass burning, and others (Zang and Morawska, 2002). In terms of particle mass concentration, combustion sources predominantly emit material in the PM 2.5 size range, while in terms of particle numbers, most of the emissions are submicrometer and ultrafine particles (Ristovski et al, 1998;CONCAWE, 1998;Morawska et al, 1999).…”
Section: Sourcesmentioning
confidence: 99%